The xenobiotic sensor PXR in a marine flatfish species (Solea senegalensis): Gene expression patterns and its regulation under different physiological conditions. (September 2017) - Marques, Carlos; Roberto, Vânia P.; Granadeiro, Luís; Trindade, Marlene; Gavaia, Paulo J.; Laizé, Vincent; Cancela, M. Leonor; Fernández, Ignacio
Abstract: The pregnane X receptor (PXR) is a nuclear receptor belonging to the NR1I sub-family and a known master regulator of xenobiotic metabolism. New roles have been recently proposed in mammals through its activation by vitamin K (VK) such as regulation of glucose metabolism, bone homeostasis, reproduction, neuronal development and cognitive capacities. In marine fish species little is known about PXR and its potential roles. Here, expression patterns of pxr transcripts and conservation of protein domains were determined in the Senegalese sole ( Solea senegalensis ), a marine flatfish model species in aquatic ecotoxicology. In addition to a full coding sequence transcript ( sspxr1 ), two variants lacking DNA and/or ligand binding domains ( sspxr2 and sspxr3 ) were also identified. The expression of sspxr1 during early development and in adult tissues was ubiquitous, but highest levels were observed in liver, intestine and skin. Expression was also detected by in situ hybridization in chondrocytes and cells from the granular and inner nuclear layers in three month old fish. Finally, sspxr1 expression was shown to be differentially regulated under physiological conditions related with fasting, VK and warfarin metabolism. The present work provides new and basic knowledge regarding pxr sequence and expression patterns in a marine flatfish species to unveil the potential impact of xenobiotics on marine fish physiology, and will allow a better and more ecosystemic environmental risk assessment of different pollutants over the marine environments with the development of reporter assays using PXR sequences from evolutionary distantly marine species (such as vertebrate and invertebrate marine species). Highlights: Different Senegalese sole PXR (ssPXR) transcript variants were identified. ssPXR encoding peptide showed a differential degree of conservation at DBD and LBD. ssPXR was highly expressed during embryonic development and pro-metamorphosis. ssPXR was expressed at specific cell types from the brain, eye, skeletal tissue and liver. ssPXR differentially expressed under fasting, pollutant and recovery conditions.